Tendon Transfer Outcome in Radial Nerve Injury: Our Experience - Nauman Hussain, Asif Ali Jatoi, Badaruddin Sahito, Javed Hussain Khaskheli, Irfan Muhammad Rajput, Imran Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of the current study was evaluation of outcome of tendon transfers in high radial nerve palsy for restoration of power and function of wrist and hand in Karachi, Pakistan. Methodology: A descriptive case series with clinical data of 17 patients was analyzed at the Department of Orthopedics Surgery at the Dr. Ruth K.M. Pfau Civil Hospital at Dow University of Health Sciences in Karachi, Pakistan, from January 2018 to December 2021. Patients who were diagnosed with high and low RNP were registered. Those with multiple injuries which might have caused considerable disability (polytrauma patients) or those suffering from brachial plexus lesions were excluded. Results: Out of seventeen patients, 14 (85%) were male while 03 (15%) were femalewith mean age of 29.5 years. There were 65% right-sided injured patients. Mean of the Disabilities of the Arm, Shoulder and Hand (DASH) scores was 11.44 ± 3.35 with 94.1% patients in minimal disability category whereas 5.88% patients moderately disable.Motor power of wrist and finger extension was significantly improved between the preoperative period and three months post-operatively, between the pre-operative period and six months. Conclusion: Tendon transfers treating radial nerve palsy have positive functional outcomes in terms of wrist extension, finger extension, and handgrip strength, as well as positive patient satisfaction as measured by Quick DASH ratings. Tendon transfers help restoring nonfunctional dangling wrist and hand into functional powerful wrist and hand. Keywords: Radial nerve palsy, tendon transfers outcome, DASH scores